O processo ensino-aprendizagem sobre medicina do sono no curso de medicina de uma universidade - Ferraz, Renata Caroline Mendonça (2020)
FERRAZ, Renata Caroline Mendonça. The teaching-learning process on sleep medicine in the medicine course of a public university. 2020. 67 f. Dissertation (Master in Health Education) - Federal University of Alagoas, Maceió, AL, 2020. Introduction: Sleep is a fundamental aspect of human life, having a restorative, energy conservation and protection function. Most sleep disorders are not detected and treated because, in general, people are unaware that this condition is clinical and treatable. The study of sleep began to have greater importance within the medical community from 1970 and since then it has grown exponentially, until the Federal Council of Medicine (CFM) in 2011 recognized Sleep Medicine as the area of activity in Brazil. Objectives: To evaluate the sleep medicine knowledge of students at the FAMED-UFAL boarding school and describe the student's view on the teaching of sleep medicine at graduation. Methodology: Study with a descriptive, quantitative and cross-sectional approach, through the application of the ASKME questionnaire (Assessing Sleep Knowledge in Medical Education), in its version validated for Portuguese, plus a questionnaire directed to the students' view of the teaching- learning about sleep medicine at the university in question. Results: 149 students from the boarding school were evaluated, 95.3% of whom had contact with the topic during graduation, predominantly in the discipline of neurology (91.2%). In the present study, eighty-six (57.7%) students obtained knowledge considered satisfactory (>60% of correct answers), that is, they answered more than 16 ASKME questions correctly. A large portion (82.8%) of students did not consider their knowledge of sleep to be satisfactory and 72% did not feel safe in caring for a patient with sleep disorder, as a general practitioner. Conclusion: Considering the scarcity of studies on the teaching of sleep medicine in Brazil, we intend to collaborate with the definition of new teaching proposals on the topic, focusing on the definition of essential knowledge and skills for a general practitioner and transversality. It is also expected to contribute to future research.